Wind Mill and Solar Energy - Ametov Bayram Tursynbaevich; Uzakbaeva Akmaral Sulayman Kizi; Allamuratov Guljamal Bisengali Kizi (Zien Journals, 2022)
Studied alternative energy sources such as solar energy and wind energy industry. The basic principle of the use of renewable energy is to extract it from processes constantly occurring in the environment and provide them for use.
Keywords: Studied alternative energy sources; energy; extract; solar